On the Use of a Computer-Assisted Annotation Model for Analyzing the Function of Literary Spaces - Spiridon-Șerbu, Claudia; Lindemann, Sofiana (Universitatea Transilvania Brasov, 2025)
The article examines the use of computer software for the analysis of literary texts, with a particular focus on investigating the functions of literary spaces. It presents an annotation model specifically developed to precisely identify and classify the literary functions of spaces in narrative texts. In doing so, not only are mechanical data recorded, but also narrative structures and patterns are uncovered that might have remained hidden in a traditional close-reading analysis.
Keywords: Computer-assisted Annotation; CATMA 6; Digital Analysis